Innovative Technologies in the Field of Education - Kh. S. Yakubova; R. B. Daminova (Scholars Digest Publishing, 2022)
The article is devoted to the need to expand the possibilities and application of modern innovative technologies in the field of secondary education in Uzbekistan. Today, our country, in the realities of the modern world, requires a qualitatively new approach to education. The direction of the reforms taking place in the sphere of preschool, primary, secondary and higher education should lead to the creation of such a system, the basis of which is formed by the ideas of self-development of the individual, expanding his opportunities in choosing his life path.